Comparative Analysis of Legal Certainty in Fiduciary Guarantees for Defaulting Visit of Justice and Economic Analysis of Law - Wennie Melannie; Suparno Suparno (International Journal of Social Service and Research, 2026)
In Indonesia, fiduciary guarantees serve as a critical mechanism for securing credit agreements by providing creditors with the right to execute collateral if debtors default. However, the issuance of Constitutional Court Decisions No. 18/PUU-XVII/2019 and No. 2/PUU-XIX/2021 has significantly altered the execution mechanism, shifting it from parate execution—direct execution without court involvement—to a mechanism that requires either mutual agreement between the creditor and debtor or a court order. This change has created legal uncertainty, particularly regarding the balance between creditor protection and debtor rights. This research aims to analyze the legal certainty of fiduciary collateral execution against defaulting debtors by integrating the perspectives of justice and the Economic Analysis of Law. The method used in this research is a normative legal approach, which examines and analyzes applicable legal provisions as well as theories related to justice and legal economics. In this context, the theory of justice is used to understand the principles of fairness that should be applied in resolving disputes over fiduciary collateral, while the Economic Analysis of Law is employed to evaluate the economic impact of legal practices related to the execution of fiduciary collateral on both creditors and debtors. The findings of this research are expected to provide insights into how the law can achieve a balance between legal certainty, justice for the parties involved, and economic efficiency in the application of fiduciary collateral execution against defaulting debtors.